THE EFFECT OF DESTINATION IMAGE AND SERVICE QUALITY TOWARD TOURISTST VISITING DECISIONS THROUGH VISITING INTEREST AS INTERVENING VARIABLE - Lustono Lustono; Ratna Suryani (Universitas Pasundan, 2022)
Tourism has a crucial role in the development of the country and has an impact on Locally-Generated Revenue (PAD) for local governments. Banjarnegara which is one of the areas in Central Java has one of the top tourist attractions, namely PD. TRM. Serulingmas. Therefore, it takes a strategy to develop it so that it can grow and increase the interest of tourists to visit. This study aims to determine the Effect of Destination Image and Service Quality on Tourist Visiting Decisions Through Visiting Interests as Intervening Variables. The population in this study were all visitors to PD. TRM. Serulingmas. The samples used in this study were 110 respondents using a non-probability sampling technique through a purposive sampling approach. Methods of data collection using documentation and questionnaires. Instrument testing is done by testing the validity and reliability test. Data analysis used SPSS 24. The results showed that the destination image and service quality influenced the decision to visit tourists through visiting interest as an intervening variable. The conclusion of this study tourists can enjoy the natural beauty and facilities in PD. TRM Serulingmas comfortably so that it can maintain an impression for visitors. The quality of service provided by the manager or company that is consistent with the expectations of customers or visitors can influence tourists so that visitors come again.